หลักการพัฒนาจิตตามแนวพระพุทธศาสนา - ใครบุตร, ทวีศักดิ์ (วารสารศรีล้านช้างปริทรรศน์, 2016)
พระพุทธศาสนามีหลักการพัฒนาจิตสำหรับผู้ที่ต้องการความหลุดพ้นจากทุกข์ในสังสารวัฏ แต่ขึ้นอยู่กับวาสนาบารมีและความเพียรพยายามของแต่ละคน หลักการพัฒนาจิตไปตามลำดับจากน้อยถึงขั้นที่ต้องใช้เวลาและความเพียรมาก ทั้งนี้ ก็เพื่อให้เหมาะสมกับจริตของแต่ละบุคคลที่ได้สั่งสมมาซึ่งเป็นไปตามกาลเวลา วิธีการนี้ท่านเรียกว่า บุญกิริยาวัตถุ ได้แก่ ทานมัย บุญสำเร็จด้วยการให้ทาน สีลมัย บุญสำเร็จด้วยการรักษาศีล ภาวนามัย บุญสำเร็จด้วยการเจริญสมาธิภาวนา การให้ทานนั้นนับว่าเป็นวิธีที่ง่ายที่สุดในการปรับสภาพจิต ใช้เวลาและความพยายามน้อยส่งผลให้จิตใจปราณีตผ่องใส เบาสบายได้ในระดับหนึ่ง การรักษาศีล สามารถทำได้โดยไม่ต้องลงทุนลงแรงอะไรเลย เพียงแค่คอยระวังไม่ให้เกิดล่วงละเมิดทางกายหรือทางวาจาเท่านั้น และการทำสมาธิ ก็คือการรวมจิตให้เป็นหนึ่ง จิตที่มีสมาธิอยู่ในสภาพที่ประณีต สะอาด สว่าง และบริสุทธิ์กว่าจิตขั้นพื้นฐานของคนทั่วไป ภาวนามัยจึงทำให้มีความสุขมากกว่าทานมัย การให้ทานและสีลมัย การรักษาศีล บุญกิริยาวัตถุ เป็นบาทฐานที่สำคัญต่อการพัฒนาคุณภาพจิตใจ เป็นการยกจิตของมนุษย์และสัตว์ให้สูงขึ้นตามลำดับจนกระทั่งบรรลุถึงเป้าหมายสูงสุดในพระพุทธศาสนาซึ่งเป็นความดีสูงสุดคือพระนิพพานได้ ดังเช่นพระพุทธเจ้า และพระอริยสงฆ์สาวกของพระพุทธเจ้าทั้งหลาย ดังนั้น ทุกคนจึงควรเห็นความสำคัญของการพัฒนาจิตหรือสมาธิภาวนาเพื่อยกระดับจิตของตนให้สูงขึ้นและประณีตขึ้นกระทั่งสามารถทำลายอาสวะกิเลสภายในจิตของตนที่เรียกว่า พระนิพพานอันเป็นจุดหมายสูงสุดตามหลักคำสอนในพระพุทธศาสนา           In Buddhism, there was the principle of mind development for whoever wished release from sufferings in transmigration, but whether each of them would attain suffering extinguishment was depended upon their past tendencies and completeness (Vasanaparami) and endeavor (Viriya). The mind development had to be conducted continuously in the descendent order in order to meet with their accumulated temperament (characteristic behavior), which was improved when the time passed by. Such an approach of merit accumulation was called bases of meritorious action (grounds for accomplishing merit), known as Punyakiriya-vatthu in Buddhism), which were comprised of meritorious action in accomplishment of generosity (Danamaya), meritorious action in accomplishment of precept observance (Silamaya), and meritorious action in accomplishment of mental development (Bhavanamaya). Giving or generosity was regarded as an easy way to cleanse human minds due to less time and less attempt. As a result, human minds became fine, clearly bright, light and comfortable to some extent. The observance of precepts could be done without any cost or attempt. It was good for who observed precepts to carefully avoid physical or verbal offences. Meditation was referred to consolidate or cumulate one’s mind into any single state. The concentrated mind was accepted to be finer, clearer, brighter and purer than common men’s minds. So, the accomplishment of mental development was said to be happier than generosity and precept observance. In addition, the bases for accomplishing merit were important grounds for mental development. Through this principle, human minds, including animals’ minds, were consecutively raised up until they, like Lord Buddha and his noble disciples, attained Nibbana, the highest goal in Buddhism. That was regarded as the sublime bliss. Therefore, mental concentration and development should be extremely recognized to level up and refine their minds until all defilements were absolutely destroyed. Then, Nibbana, the mental state that was accepted the supreme target in Buddhism was certainly attained.